Increased expression of TROP2 in airway basal cells potentially contributes to airway remodeling in chronic obstructive pulmonary disease. Issue 1 (December 2016) - Liu, Qixiao; Li, Haijun; Wang, Qin; Zhang, Yuke; Wang, Wei; Dou, Shuang; Xiao, Wei
Abstract Background The airway epithelium of chronic obstructive pulmonary disease (COPD) patients undergoes aberrant repair and remodeling after repetitive injury following exposure to environmental factors. Abnormal airway regeneration observed in COPD is thought to originate in the stem/progenitor cells of the airway epithelium, the basal cells (BCs). However, the molecular mechanisms underlying these changes remain unknown. Here, trophoblast cell surface antigen 2 (TROP2), a protein implicated in the regulation of stem cell activity, was examined in lung tissue samples from COPD patients. Methods The expression of TROP2 and hyperplasia index Ki67 was assessed in lung epithelium specimens from non-smokers (n = 24), smokers (n = 24) and smokers with COPD (n = 24). Primary airway BCs were isolated by bronchoscopy from healthy individuals and COPD patients and subsequently transfected with pcDNA3.1-TROP2 or siRNA sequence in vitro. The functional consequences of TROP2 overexpression in BCs were explored. Results Immunohistochemistry and immunofluorescence revealed increased TROP2 expression in airway BCs in smokers with COPD compared to nonsmokers and smokers without COPD, and staining was highly localized to hyperplastic regions containing Ki67 positive cells. TROP2 expression was also inversely correlated with airflow limitation in patients with COPD (r = −0.53, P < 0.01). pcDNA3.1-TROP2-BCs in vitro exhibited improved proliferation with activation of ERK1/2 phosphorylation signaling pathway. In parallel, changes in vimentin and E-cadherin in pcDNA3.1-TROP2-BCs were consistent with an epithelial-mesenchymal transition (EMT)-like change, and secretion of inflammatory factors IL-1β, IL-8 and IL-6 was increased. Moreover, down-regulation of TROP2 by siRNA significantly attenuated the proliferation of BCs derived from COPD patients. EMT-like features and cytokine levels of COPD basal cells were also weakened following the down-regulation of TROP2. Conclusion The results indicate that TROP2 may play a crucial role in COPD by affecting BC function and thus airway remodeling through increased BC hyperplasia, EMT-like change, and introduction of inflammatory molecules into the microenvironment.